STUDENT PERCEPTION OF ENGLISH LANGUAGE LEARNING STRATEGIES: A COMPARATIVE STUDY OF TRADITIONAL AND MODERN METHODS - Salainti, Engelina; Fansury, Andi Hamzah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aimed to investigate the students' perception of Learning English strategies in traditional and modern methods, with the main goal being to understand the preferences and the effectiveness they felt. The Traditional method, such as lecture-based instruction and doing exercises from textbooks, has been used for a long time in the English language learning process, while modern methods, including digital tools and interactive activity in learning, become more popular. The surveys and interviews with the students from Universitas Klabat which has different background majors who took General English classes in 2023/2024-year program, this investigation explores the students' perception of traditional and modern methods in the learning process. The findings showed that nevertheless, the Traditional method was acknowledged considering that it was structured and its detailed explication, on the other hand, the students considered that the modern method was more interesting and conducive to interactive learning. This study gave insights into the strengths and limitations of both methods and offered recommendations to integrate traditional and modern strategies to improve English Education.